Circulating miRNA-21 is an innovative biomarker for cardiovascular events in erectile dysfunction patients - Agulló, Laura; Segura, Ana; Ortuño-Miquel, Samanta; Brinca, Ana Teresa; Micol-Ponce, Rosa; Arrarte, Vicente; Ponce, María Rosa; Miró-Martínez, Pau; Zandonai, Thomas; Peiró, Ana M. (Frontiers in Cardiovascular Medicine, 2024)
It is well-known that circulating microRNAs (miRNAs) play a relevant role in many kinds of diseases by regulating the expression of those genes involved in various pathophysiologic processes, including erectile dysfunction (ED) and cardiovascular diseases (CVDs).Purpose: Identify the miRNA-21 profile in the blood samples of patients with ED, CVDs, and the combination of both pathologies, to elucidate the potential function of miRNA-21.Methods: Of 45 CVDs patients and/or subjected to the erectile function test, subjects were divided into cases:CVDs with ED (cases, n=29) and controls (n=16) with either ED or CVDs. A real-time polymerase chain reaction (PCR) analysis verified the results. MiRNA-21 expression was quantified, and an informatics analysis was applied to predict the functions of this differentially expressed miRNA-21.Results: 64% of cases (63±9 years, 66% severe ED, 56% CV ejection fraction) debuted before with ED as sentinel clinical manifestation. Here the serum miRNA-21 levels of the control ED were significant and by up to 10-fold higher than the CVDs controls and cases. A significant inverse (p = 0.0368, β = -2.046) correlation was found between erectile function and miRNA-21 levels.Our study provides comprehensive insights into the functional interaction between miRNA-21 and ED in CVDs patients. Its relevance lies in the potential of miRNA as a biomarker to be applied in the cardiovascular predictive medicine field.